Identification of Forensic Odontology in Investigation Case of Human Skeletal Findings: Case Report - Fitri Rizki Amalia; Farah Primadani Kaurow; Nurtami Soedarsono; Elza Ibrahim Auerkari (Newinera Publisher, 2025)
The objective of forensic identification is to assist investigators in identifying an individual's identity, Through the identification process in forensic odontology, we can obtain information related to a person's identity such as race, gender, age and oral habits. This case report discusses the identification of skeletal found by residents in a garbage dump. This discovery was reported to the police in charge for further investigation. These skeletals were identified by a joint team, consist of forensic pathologist and forensic odontologist. In this case, we conclude the skeletals was human skeletals, mongoloid male with estimation of age between 30-50 years old.